When the Words are Not Everything: The Use of Laughter, Fillers, Back-Channel, Silence, and Overlapping Speech in Phone Calls - Vinciarelli, Alessandro; Chatziioannou, Paraskevi; Esposito, Anna (Frontiers in ICT, 2015)
This article presents an observational study on how some common conversational cues - laughter, fillers, back-channel, silence, and overlapping speech - are used during mobile phone conversations. The observations are performed over the SSPNet Mobile Corpus, a collection of 60 calls between pairs of unacquainted individuals (120 subjects for roughly 12 hours of material in total). The results show that the temporal distribution of the social signals above is not uniform, but it rather reflects the social meaning they carry and convey. In particular, the results show significant use differences depending on factors such as gender, role (caller or receiver), topic, mode of interaction (agreement or disagreement), personality traits and conflict handling style.